The Influence of Environmental, Social and Governance and the Risk of Financial Information Disclosure on Investment Efficiency in Environmentally Sensitive Industrial Companies in ASEAN 5 Period 2018-2022 - Eka Irianingsih; Gatot Nazir Ahmad; Agung Dharmawan Buchdadi (Lafadz Jaya Publisher, 2024)
The aim of this research is to examine the effect of Environmental, Social, and Governance (ESG) disclosure and Financial Information Disclosure on Investment Efficiency where the variables used in this research are the dependent variable (Investment Efficiency), the independent variable (ESG and Risk of Financial Information Disclosure) and control variables (Tangible, Leverage, Company Performance). The population in this study are environmentally sensitive industrial companies in ASEAN 5 which have active status and are listed on the Indonesia Stock Exchange (IDX), Singapore Stock Exchange (SGX), Malaysia Stock Exchange (MYX), Philippine Stock Exchange (PSE), and Stock Exchange Thailand (SET) for the period 2018 – 2022. Sampling was carried out by purposive sampling. Based on purposive sampling in sample selection, 250 research samples were obtained for five consecutive years. The findings of this research indicate that Environmental, Social, and Governance (ESG) has no effect on investment efficiency. Meanwhile, the Risk of Financial Information Disclosure has a positive and significant effect on investment efficiency.